HIV counseling, testing, and test result receipt among East African women of reproductive age using recent national health surveys - Terefe, Bewuketu (Frontiers in Reproductive Health, 2024)
Introduction: One of the most important public health concerns is still the HIV/AIDS, particularly in developing countries. Although HIV testing is an important, its uptake remains low, and no study has looked into the scale of HIV counseling, testing, and test result receipt. Therefore, this study aimed to investigated HIV counseling, testing, and test result receipt, as well as the factors that influence them, among East African women.Methods: This analysis used DHS data from 10 East African countries. We examined the coverage of HIV counseling, testing, and test result receipt among East African women, and factors. To select candidate factors related to the outcome variable, binary and multiple logistic regression analyses were conducted, and the results were presented using adjusted odds ratios (AORs) with 95% confidence intervals. In the binary and multiple logistic regression analyses, P values of < 0.2 and <0.05 were used to assess significant variables, respectively.Results: A total of 41,627 weighted women included to this study. HIV counseling, testing, and test result receipt among East African women were found to be 77.86% (95% CI=77.46,78.26). Being 25-34 years old (AOR=1.13, 95% CI, 1.06,1.21), 35-49 years old (AOR=1.15, 95% CI, 1.05,1.26) as compared to 15-24 years old women, primary education (AOR=1.75, 95% CI, 1.64,1.86), secondary/higher education level (AOR=1.96, 95% CI, 1.82,2.13) as compared to not educated women, poor, (AOR=1.22, 95% CI,1.14,1.29), middle wealth (AOR=1.12,95%CI,1.04,1.21) as compared to rich wealth index, mass media exposure (AOR=1.29,95% CI, 1.22,1.35), 3-5 parity (AOR=1.29, 95% CI, 1.21,1.37), more than 5 parity (AOR=1.46, 95% CI,1.33,1.61) as compared to <3 parity, health institution delivery (AOR=1.65,95% CI,1.53,1.76), were associated positively with the outcome variable respectively.However, being married (AOR=0.79, 95% CI, 0.72,0.87), not using contraceptive (AOR=0.58,95% CI,0.51,0.61), and traditional contraceptive method user (AOR=0.47, 95% CI, 0.41,0.54) as compared to modern users were associated negatively with outcome variable respectively.This study found that HIV counseling, testing, and test result receipt are still unsatisfactory. Strengthening maternal health services such as institutional delivery, family planning, and women's empowerment, as well as changing mass media and taking advantage of these opportunities, will boost the region's coverage of HIV counseling, testing, and obtaining results.